2015
DOI: 10.1001/jamainternmed.2015.0225
|View full text |Cite
|
Sign up to set email alerts
|

Exercise and Vitamin D in Fall Prevention Among Older Women

Abstract: IMPORTANCE While vitamin D supplementation and exercise are recommended for prevention of falls for older people, results regarding these 2 factors are contradictory. OBJECTIVE To determine the effectiveness of targeted exercise training and vitamin D supplementation in reducing falls and injurious falls among older women. DESIGN, SETTING, AND PARTICIPANTSA 2-year randomized, double-blind, placebo-controlled vitamin D and open exercise trial conducted between April 2010 and March 2013 in Tampere, Finland. Par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
302
3
6

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 240 publications
(323 citation statements)
references
References 33 publications
12
302
3
6
Order By: Relevance
“…However, the level of impacts produced was not generally recorded in previous interventional studies in this age group, and it is unclear how comparable these were to the present aerobics class in terms of delivery of osteogenic PA. In contrast, previous well-conducted exercise intervention studies in older adults have found some evidence of benefit in preventing fall-related fractures, yet no positive effect on BMD (Korpelainen, Keinanen-Kiukaanniemi, Heikkinen, Vaananen, & Korpelainen, 2006;Uusi-Rasi et al, 2015). Whereas these negative studies could be a reflection of the types of exercise used, our results suggest that participant characteristics might also play a role.…”
Section: Discussioncontrasting
confidence: 99%
“…However, the level of impacts produced was not generally recorded in previous interventional studies in this age group, and it is unclear how comparable these were to the present aerobics class in terms of delivery of osteogenic PA. In contrast, previous well-conducted exercise intervention studies in older adults have found some evidence of benefit in preventing fall-related fractures, yet no positive effect on BMD (Korpelainen, Keinanen-Kiukaanniemi, Heikkinen, Vaananen, & Korpelainen, 2006;Uusi-Rasi et al, 2015). Whereas these negative studies could be a reflection of the types of exercise used, our results suggest that participant characteristics might also play a role.…”
Section: Discussioncontrasting
confidence: 99%
“…77 Thus, vitamin D supplementation at daily doses of 800 to 1,000 IU consistently demonstrated beneficial effects on strength and balance, 78 vitamin D supplementation in general notably strengthening quadriceps power. 79,80 It should be noted, however, that regarding the efficacy and the degree of the beneficial effects of vitamin D supplementation on muscle strength and balance as a general rule, it appears that the priorto-treatment levels of vitamin D are of paramount importance. Indeed, the higher the pretreatment levels, the lesser the magnitude of the benefits, i.e.…”
Section: Effect Of Vitamin D Supplementation On the Efficacy Of Exercmentioning
confidence: 99%
“…Exercise may reduce FoF by improving strength, gait, balance, and mood, and by reducing the occurrence of falls and injurious falls [12,13]. A recent Cochrane review found that exercise interventions may reduce FoF immediately after intervention, although the effect may be temporary [6].…”
Section: Introductionmentioning
confidence: 99%